Faktor-Faktor Yang Mempengaruhi Peningkatan Penjualan Shopee Seller Center di Ane Store Official - Ema Dwi Ariski; Eny Setyariningsih; Toto Heru Dwihandoko (BISMA : Business and Management Journal, 2025)
The development of digital technology has significantly impacted the trade sector, especially in e-commerce. Shopee, as one of the leading platforms, offers the Shopee  Seller Center feature to support sales activities. This study aims to analyze the factors influencing the increase in sales at AnE Store Official. The research method used is quantitative with a factor analysis approach (Principal Component Analysis). The results show that seven main factors affect sales growth: product quality and appeal, pricing and accessibility, digital promotion strategies, product design comfort, customer service, and optimal use of Shopee features. This research contributes to helping business actors formulate effective digital marketing strategies.